Determinants of Investment Decisions in the Capital Market During the COVID-19 Pandemic - Erni Suryandari Fathmaningrum; Tiyas Puji Utami (Journal of Accounting and Investment, 2022)
Research aims: This study aims to determine the effect of herding behavior, accounting information, and information technology on investment decisions through investment interest during the COVID-19 pandemic.Design/Methodology/Approach: Using the purposive sampling method, this study used a sample of investors who had just invested in the Indonesian capital market during the COVID-19 pandemic. This quantitative study employed primary data based on questionnaires distributed to respondents via the internet. Respondents in this study were 241 investors. Hypothesis testing in this study utilized SEM-PLS analysis through the SMART PLS 3.0 application.Research findings: The results showed that herding behavior did not affect investment decisions through investment interest in the capital market during the COVID-19 pandemic. Meanwhile, accounting information and technology information influenced investment decisions through investment interest in the capital market during the COVID-19 pandemic.Theoretical contribution/Originality: The study results contribute to the literature (body of knowledge), especially as additional discussion toward theory and literature related to herding behavior, accounting information, and information technology on investors decisions through investment interest to invest in the capital market, which is still very limited.